Brief report: Cause of death among people discharged from infective endocarditis related hospitalization—West Virginia, 2016–2019. Issue 5 (9th March 2022) - Dai, Zheng; Smith, Gordon S.; Hendricks, Brian; Bhandari, Ruchi
Abstract: Background and Objectives: Compare proportion of all‐cause and cause‐specific mortality among West Virginia Medicaid enrollees who were discharged from infective endocarditis (IE) hospitalization with and without opioid use disorder (OUD) diagnosis. Methods: The proportions of cause‐specific deaths among those who were discharged from IE‐related hospitalizations were compared by OUD diagnosis. Results: The top three underlying causes of death discharged from IE hospitalization were accidental drug poisoning, mental and behavioral disorders due to polysubstance use, and cardiovascular diseases. Of the total deaths occurring among patients discharged after IE‐related hospitalization, the proportion has increased seven times from 2016 to 2019 among the OUD deaths while it doubled among the non‐OUD deaths. Discussion and Conclusions: Of the total deaths occurring among patients discharged after IE‐related hospitalization, the increase is higher in those with OUD diagnosis. OUD is becoming a significantly negative impactor on the survival outcome among IE patients. It is of growing importance to deliver medication for OUD treatment and harm reduction efforts to IE patients in a timely manner, especially as the COVID‐19 pandemic persists.